EFFECT OF BLACK RICE BRAN EXTRACT (Black Rice Bran) TO DECREASE DECREASE OF GLUCOSE LEVEL IN DIABETIC RATS - Sari, Novita; Wahyuni, Arifah Sri (Pharmacon: Jurnal Farmasi Indonesia, 2017)
Black rice bran is one of processed foods derived from plants and has a decreasing effect of blood glucoselevels. Major component of anthocyanin in black rice bran that functions in lowering blood glucoseconcentration is cyanidin 3-glucoside. Fifteen male rats Sprague-Dawley strain were selected randomly anddivided into 5 groups with the same number in each groups. These groups were consisted of normal control,negative control, and black rice bran extract treatment with dose of 50, 100 and 200 mg/kg of bodyweight(b.w.). Each of them were induced to experience diabetes by alloxan 150 mg/kg of b.w. Measurement ofblood glucose levels was done by using visible spectrophotometer at 546 nm. The samples were collectedbefore and after alloxan injection, and after 4, 7, and 10 days later to observe the changes of blood glucoselevels. The results showed that black rice bran at 200 mg/kg of b.w. was able to lower the glucose levels,which amounted for 131,33 ± 8,08 mg/dL after 10 days of injection.